DIGITAL LITERACY ATTITUDES AMONG EFL PRE-SERVICE TEACHERS IN THE DEVELOPMENT OF LEARNING MEDIA - Dila Charisma; Rudi Hartono; Sri Wahyuni (Indonesian EFL Journal, 2025)
This study investigates the digital literacy attitudes of seventh-semester EFL pre-service teachers at one Muhammadiyah University in West Java, focusing on their experiences, challenges, and needs in utilizing digital tools for instructional purposes. While digital literacy is increasingly recognized as a crucial skill in modern education, many pre-service teachers face significant obstacles, including limited technical proficiency, difficulty in accessing credible online resources, and a lack of understanding of ethical considerations in digital content creation. Employing a qualitative approach through open-ended questionnaires and semi-structured interviews, this research explores participants’ perspectives on using digital tools such as Canva and Wordwall in developing learning media. The findings reveal that although pre-service teachers are enthusiastic about incorporating technology into their teaching practices, technical difficulties and ethical concerns often hinder their efforts. Participants emphasized the need for more practical training, hands-on workshops, and ethical guidelines to enhance their digital literacy competencies. The study highlights the importance of integrating structured digital literacy training into teacher education programs, ensuring that future educators are well-equipped to design engaging and pedagogically sound instructional media. Addressing these challenges will ultimately contribute to improving the quality of EFL teaching and fostering a more technology-integrated learning environment.